2010
DOI: 10.1038/leu.2010.141
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD22-MCC-DM1: an antibody-drug conjugate with a stable linker for the treatment of non-Hodgkin's lymphoma

Abstract: Antibody-drug conjugates (ADCs) are potent cytotoxic drugs linked to antibodies through chemical linkers, and allow specific targeting of drugs to neoplastic cells. The expression of CD22 is limited to B-cells, and we show that CD22 is expressed on the vast majority of non-Hodgkin's lymphomas (NHLs). An ideal target for an ADC for the treatment of NHL would have limited expression outside the B-cell compartment and be highly effective against NHL. We generated an ADC consisting of a humanized anti-CD22 antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 22 publications
(27 reference statements)
0
71
0
Order By: Relevance
“…The antibody anti-CD22 10F4 has been previously identified as an antibody to CD22 that is particularly effective as an ADC compared with other anti-CD22 antibodies when tested in xenograft models (6). The humanized form of 10F4 (MCDT2219A; Hu10F4; ref.…”
Section: Generation and Characterization Of Dcdt2980smentioning
confidence: 99%
See 3 more Smart Citations
“…The antibody anti-CD22 10F4 has been previously identified as an antibody to CD22 that is particularly effective as an ADC compared with other anti-CD22 antibodies when tested in xenograft models (6). The humanized form of 10F4 (MCDT2219A; Hu10F4; ref.…”
Section: Generation and Characterization Of Dcdt2980smentioning
confidence: 99%
“…The humanized form of 10F4 (MCDT2219A; Hu10F4; ref. 6) was conjugated to MC-vc-PAB-MMAE though the interchain disulfide cysteines (Fig. 1A) as previously described (14).…”
Section: Generation and Characterization Of Dcdt2980smentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 Numerous studies indicated maytansinoid DM1 (derivative of maytansine), a highly potent microtubule polymerization inhibitor, was an ideal payload for developing ADC. [17][18][19][20] Furthermore, antibody-DM1 conjugates have shown promising results in preclinical and clinical evaluations. 21 As a member of the EGFR family, HER2 is a clinically validated ADC target.…”
Section: Introductionmentioning
confidence: 99%